A Shift in Myeloid Cell Phenotype via Down Regulation of Siglec-1 in Island Macrophages of Bone Marrow Is Associated With Decreased Late Erythroblasts Seen in Anemia of Critical Illness - Hasan, Shirin; Johnson, Maria Camargo; Kini, Ameet R.; Baldea, Anthony J.; Muthumalaiappan, Kuzhali (Frontiers in Medicine, 2019)
Burn injury has been shown to significantly dampen erythropoiesis in both burn patients and in murine models. Our previous findings elucidated the erythropoietin independent defects in red cell development stages involving erythroid progenitor production and late stage erythroblast enucleation processes. We hypothesized that macrophages (MØ) in erythroblast islands (EBI) could be yet another roadblock impeding erythropoiesis following burn injury. Here we highlight that the methodology to study EBI can be achieved with single cell suspensions using a simple technique such as flow cytometry, as obtaining the central erythroblast island macrophages (EBIMØs) of interest is a delicate process. We elucidated the requisite of EBIMØ from the erythroblast as well as the MØ perspective. In addition to the primary erythropoiesis organ, the bone marrow (BM), spleens were also examined for extra-medullary erythropoiesis. Femurs and spleens were harvested from adult mice (B6D2F1) subjected to 15% total body surface area (TBSA) scald burn (B) or sham burn (S). Total bone marrow cells (TBM) and splenocytes were probed for total erythrons, early and late erythroblasts and EBIMØ by flow cytometry. There was only a marginal increase in the number of EBIMØ after burn, but, between the signatures of EBIMØ, Siglec-1 expression (MFI) was reduced by 40% in B with and a parallel 44% decrease in TBM erythrons in the BM. There were more (2.5-fold) EEBs and less LEBs (2.4-fold) per million TBM cells in B; with a corresponding decrease in Siglec-1 and Ly6G expressions in EBIMØ associated with EEB. Conversely, extra-medullary erythropoiesis was robust in spleens from B. Not only were the numbers of EBIMØs increased in B (p < 0.002), both EEBs and LEBs associated with EBIMØ were higher by 30 and 75%, respectively. Importantly, an increase in Siglec-1 and Vcam1 expressing F480+ splenic macrophages was observed after burn injury. Therefore, stagnant EEBs in the BM after burn injury could be due to low Siglec1 expressing EBIMØ, which perhaps impede their maturation into LEBs and reticulocytes. Repercussion of myeloid cell phenotype specific to BM after burn injury could plausibly account for a defective late stage RBC maturation resulting in anemia of critical illness. Summary Sentence: Characterization of erythroblast island macrophages (EBIMØ) in the bone marrow and spleen at different stages of erythropoiesis after burn injury.